(3GdHQeLI HdZI GdJLejY (B/s - (3HSjhfj, YHO GdMejOs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2004)
(3JegjO GdHQeLI HdZI GdJLejY(B- (3GdYJGO hGdHQeLI(B- (3HQfGeL GdeUMM(B- (3JYQja hfbd GdHjGfGJ(B- (3JMce GdHQGeL(B- (3eYGdLI GdTGTI hdhMI GdeaGJjM(B- (3GdeYGdLI GdeJbOeI ddTGTI(B- (3GdSdGSd hGdLOGhd(B-(3GdYedjGJ GdMSGHjI(B- (3JfXje JNRjf GdGbQGU(B- (3GdWHGYI heYGdLI GdaCQI(B- (3GdeGcQh hGdQHW eY GdHQGeL GdaQYjI(B- (3EOGQI PGcQI fXGe OhS(B- (3GdYhGed hGdJhLjgGJ(B- (3GdJYdjeGJ(B.s
(3GdeQGLY U(B.587s
Keywords: (3GdHQeLjGJs; (3GdMGSHGJ GdEdcJQhfjIs; (3dZGJ GdJLejYs